2013
DOI: 10.1111/j.1348-0421.2012.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year survey (2007–2011) of enteric viruses in Korean aquatic environments and the use of coliforms as viral indicators

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…4, Jurzik et al 2010). However, regression analyses revealed no significant correlations between concentrations of TC and FC in relation to concentrations of AdVs, similarly to what has happened in other studies (Choi and Jiang 2005;Jurzik et al 2010;Lee et al 2013). Therefore, there was no significant quantitative correlation which concludes that TC and FC, although considered to be indicator microorganisms, are not suitable to indicate the presence of viruses in environmental samples, since the absence of TC and FC does not ensure the absence of enteric viruses (Tavares et al 2005;Jurzik et al 2010), in view of its high strength and resistance to inactivating environmental factors.…”
Section: Statistical Analysis Of Various Environmental Parameterssupporting
confidence: 81%
See 2 more Smart Citations
“…4, Jurzik et al 2010). However, regression analyses revealed no significant correlations between concentrations of TC and FC in relation to concentrations of AdVs, similarly to what has happened in other studies (Choi and Jiang 2005;Jurzik et al 2010;Lee et al 2013). Therefore, there was no significant quantitative correlation which concludes that TC and FC, although considered to be indicator microorganisms, are not suitable to indicate the presence of viruses in environmental samples, since the absence of TC and FC does not ensure the absence of enteric viruses (Tavares et al 2005;Jurzik et al 2010), in view of its high strength and resistance to inactivating environmental factors.…”
Section: Statistical Analysis Of Various Environmental Parameterssupporting
confidence: 81%
“…Yates et al (1985) have found that the survival of viruses in soil and water did not correlate with pH, concentration of nitrates, turbidity, or hardness in samples obtained from various sources in the US; temperature was the only variable that was found to be related to MS2 phage survival. Lee et al (2013) have demonstrated that the presence of enteric viruses, TC and FC, was not correlated with temperature and turbidity; TC and FC were also not related to the presence of EVs in a study conducted with surface water in South Korea over a period of 4 years. Miagostovich et al (2014) assessed the presence of viruses with temperature, conductivity, DO, turbidity, and pH and found only a correlation between viruses and turbidity and between with two areas of environmental preservation in Brazil.…”
Section: Statistical Analysis Of Various Environmental Parametersmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, Lee et al . () and Hörman et al . () found no correlation between turbidity and the presence of enteric viruses in aquatic environments.…”
Section: Discussionmentioning
confidence: 87%
“…Forty nine percent of samples were human virus-positive. In comparison, reviewing more than two dozen published studies on human viruses in rivers, the occurrence rate typically reported for virus-positive samples was 30% to 80% (Kishida et al, 2012;Lee et al, 2013) and some studies report 100% of their river samples were virus positive. Samples from urban rivers in Barcelona, Spain and Rio Janeiro, Brazil (Calgua et al, 2013), the Ruhr and Rhine rivers in Germany (Hamza et al, 2009), and the Mille-Iles river in Quebec, Canada (Payment et al, 1988), were all positive for at least one type of human enteric virus; every sample of eight from the Maas and Waal rivers in the Netherlands contained four viruses: enterovirus, norovirus, reovirus, and rotavirus (Lodder and de Roda Husman, 2005).…”
Section: Discussionmentioning
confidence: 99%